Fungsi Organisasi Pada Manajemen Proyek - Agung Wijoyo; Aang Kunaefi; David Kurniawan; Mohamad Zainudin; Muhammad Afi Gustamal; Otih Sulistiana (CV. Multi Kreasi Media, 2024)
Writing this scientific paper aims to analyze how good organizational management can help improve overall project performance. Project management can be said to be the main key that can lead to success in carrying out and completing a project to be worked on. In project management, the most important thing is to use all available constraints, time, quality, and budget to achieve all of the project's ultimate goals. By using the method of literature review (library research), the discussion of the problem is based on the opinions of experts and the results of their research. From the results of project management research conducted to provide better quality. As well as in project organizations, work can be carried out in full preparation and there is no overlapping work time.